Merger and Acquisition of Banks and Financial Institutions in Nepal: Laws and Practices - Adhikari, Arbind Kumar (KDCBAR Law Journal, 2025)
The Nepalese financial sector is experiencing a significant increase in mergers and acquisitions (M&A) due to regulatory directives and market dynamics. This article provides a detailed analysis of the legal framework and practical processes involved in these consolidations, examining the step-by-step merger process, key Nepalese laws, and the concept and practice of mergers. It also discusses the potential benefits, procedures for concluding a merger, and the critical integration process, offering a concise yet comprehensive understanding of BFI mergers in Nepal. Finally, the potential benefits of mergers within the specific context of Nepal, the procedures for concluding a merger, and the subsequent critical integration process will be discussed, offering a concise yet comprehensive understanding of BFI mergers in Nepal.